2023
DOI: 10.5194/amt-16-3881-2023
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of the Portable Ice Nucleation Chamber 2 (PINCii)

Dimitri Castarède,
Zoé Brasseur,
Yusheng Wu
et al.

Abstract: Abstract. The Portable Ice Nucleation Chamber 2 (PINCii) is a newly developed continuous flow diffusion chamber (CFDC) for measuring ice nucleating particles (INPs). PINCii is a vertically oriented parallel-plate CFDC that has been engineered to improve upon the limitations of previous generations of CFDCs. This work presents a detailed description of the PINCii instrument and the upgrades that make it unique compared with other operational CFDCs. The PINCii design offers several possibilities for improved INP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…At temperatures warmer than required for homogeneous freezing, ice nucleation was not observed below water saturation. Data collected at around 26°C show that all onsets are around droplet breakthrough conditions (gray dashed line), which was experimentally determined for various PINCii operating conditions by Castarède et al (2023). Droplet breakthrough characterizes a threshold in the T-RH i parameter space wherein unfrozen droplets continue to grow to detectable sizes for the OPC, thus inhibiting phase discrimination.…”
Section: In Activitymentioning
confidence: 89%
See 4 more Smart Citations
“…At temperatures warmer than required for homogeneous freezing, ice nucleation was not observed below water saturation. Data collected at around 26°C show that all onsets are around droplet breakthrough conditions (gray dashed line), which was experimentally determined for various PINCii operating conditions by Castarède et al (2023). Droplet breakthrough characterizes a threshold in the T-RH i parameter space wherein unfrozen droplets continue to grow to detectable sizes for the OPC, thus inhibiting phase discrimination.…”
Section: In Activitymentioning
confidence: 89%
“…A strong reduction in EF PN was observed when switching from non-compliant HiS to SECAcompliant LoS, which agrees with other studies that have shown large reductions in particle number emissions Freezing onsets were determined where the frozen fraction between ice crystals (>3 μm) and the total particle number concentrations exceeded 1%. The solid blue line indicates water saturation, the dashed black line represents the homogeneous freezing threshold for 200 nm particles according to Koop et al (2000) (calculated with a water activity (Δa w ) of 0.2946) and the gray dashed line represents the experimentally determined droplet breakthrough conditions of PINCii (Castarède et al, 2023).…”
Section: Emission Factors-pn Pm and Ccnmentioning
confidence: 99%
See 3 more Smart Citations